2014
DOI: 10.1007/s00467-014-2814-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of albuminuria in the follow-up of HIV-infected pediatric patients

Abstract: Mild proteinuria affected approximately one fifth of patients in our cohort. The determination of albuminuria allowed the differentiation between glomerular and tubular proteinuria, although no relationship with metabolic comorbidities was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…GFR was also normal with no difference between those with or without HIV. Other cohorts have reported similar findings [13,14,26].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…GFR was also normal with no difference between those with or without HIV. Other cohorts have reported similar findings [13,14,26].…”
Section: Discussionsupporting
confidence: 74%
“…Other studies have reported a prevalence of microalbuminuria between 10 and 30% in African HIV+ children [12,13,17]. The lower prevalence found in this cohort could be due to children starting ART relatively earlier than in other African cohorts, or fewer children receiving a TDF-based regimen.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…5,6 However, persistent renal function abnormalities occur in one fifth of HIV-infected children and are associated with improved survival, black race and Hispanic ethnicity and exposure to nephrotoxic drugs. 7,8 Current recommendations in children and adolescents with HIV and no previous evidence of kidney disease suggest screening for renal dysfunction with estimated glomerular filtration rate (GFR) at HAART initiation or change and at least twice yearly, and for kidney damage (urinalysis or quantitative proteinuria) at HAART initiation or change and at least yearly 5,9 or, if the patient is receiving tenofovir, at shorter intervals (3-6 months). 6 The best method for estimating GFR in children remains uncertain.…”
mentioning
confidence: 99%